Genetic Diversity of Phyllanthus emblica From Two Different Climate Type Areas - Liu, Xiongfang; Ma, Yongpeng; Wan, Youming; Li, Zhenghong; Ma, Hong (Frontiers in Plant Science, 2020)
Phyllanthus emblica L. is a well-known medicinal and edible plant species. Various medicinal compounds in the fruit make it an important medicinal and promising economic material. The plant is widely distributed in Southwestern and Southern China. However, due to massive deforestation and land reclamation as well as deterioration of its natural habitat in recent years, the wild resources of this species have been sharply reduced, and it is rare to see large-scale wild P. emblica forests so far. In order to effectively protect and rationally utilize this species, we investigated the genetic diversity, genetic structure, and population dynamics of 260 individuals from 10 populations of P. emblica sampled from the dry climate area in Yunnan and wet climate area in Guangxi using 20 polymorphic EST-SSR markers. We found high genetic diversity at the species level (He = 0.796) and within populations (He = 0.792), but low genetic differentiation among populations (FST = 0.084). In addition, most genetic variation existed within populations (92.44%) compared with variation among the populations (7.56%). Meanwhile, the NJ tree, STRUCTURE, and hierarchical analysis suggested that the sampled individuals were clustered into two distinct genetic groups. In contrast, the genetic diversity of the dry climate group (He = 0.786, Na = 11.790, I = 1.962) was higher than that of the wet climate group (He = 0.673, Na = 9.060, I = 1.555), which might be attributed to the combined effects of altitude, precipitation, and geographic distance. Interestingly, only altitude and precipitation had significant pure effects on the genetic diversity, and the former was slightly stronger. In addition, DIYABC analysis suggested the effective population size of P. emblica might have contracted in the beginning of the Last Glacial Maximum. These genetic features provided vital information for the conservation and sustainable development of genetic resources of P. emblica, and they also provided new insights and guidelines for ecological restoration and economic development in dry-hot valleys of Yunnan and karst areas in Guangxi.